The quantitative easing in China - Nie, Dapeng (2016)
In this thesis we analyze the recent events in China, as far as the aggressive attitude of the Central Bank of China（People’s Bank of China, PBC in brief） is concerned towards avoiding the slowdown of the economy and the alleged possibility of its entry into deflation territory and the Zero Lower Bound. In the western way of looking into this problem, our major task is closely related to question whether Quantitative Easing (QE) in China seems to be (or no to be) of any usefulness at all. As we all know very well by now, many economists, top central banks officials, commentators and international institutions (like the IMF) are coming to realize the clear limits of monetary policy and QE in many developed western and Asian economies like Japan. After a long period having central banks creating money to unbelievable levels, many are now calling for the return of active fiscal policy. In our case, and using a linear VAR model, we can conclude in the opposite direction for the Chinese case. Using the multipliers associated with inflation, we can conclude that real variables (like residential investment) show a rather small positive cumulative impact upon inflation, while wealth variables (like the Stock Market Index) show a rather small negative impact. Instead, it is the creation of money (Monetary Base) that displays a huge impact upon inflation. If the Monetary Base increases (first difference of its logarithmic value) by one standard deviation, the change in the CPI will be increased by 14.53 after just nine quarters. Therefore, deflation and the stringent limitations of monetary policy in the Zero Lower Bound do not seem to be applying to the Chinese economy by now, as well as the near future is concerned. Obviously, we are not suggesting that, due to this result, active fiscal policy should not also be used in order to achieve the general goals of economic policy in China.